Phytoplankton and the Macondo oil spill: A comparison of the 2010 phytoplankton assemblage to baseline conditions on the Louisiana shelf. (December 2015) - Parsons, M.L.; Morrison, W.; Rabalais, N.N.; Turner, R.E.; Tyre, K.N.
Abstract: The Macondo oil spill was likely the largest oil spill to ever occur in United States territorial waters. We report herein our findings comparing the available baseline phytoplankton data from coastal waters west of the Mississippi River, and samples collected monthly from the same sampling stations, during and after the oil spill (May–October, 2010). Our results indicate that overall, the phytoplankton abundance was 85% lower in 2010 versus the baseline, and that the species composition of the phytoplankton community moved towards diatoms and cyanobacteria and away from ciliates and phytoflagellates. The results of this study reaffirm the view that phytoplankton responses will vary by the seasonal timing of the oil spill and the specific composition of the spilled oil. The trophic impacts of the purported lower abundance of phytoplankton in 2010 coupled with the observed assemblage shift remain unknown. Highlights: Phytoplankton biomass was 85% lower in 2010 versus baseline. The phytoplankton community moved towards diatoms and cyanobacteria and away from ciliates and phytoflagellates. Trophic impacts remain unknown. Abstract : Phytoplankton biomass was 85% lower in 2010 versus baseline. The phytoplankton community moved towards diatoms and cyanobacteria and away from ciliates and phytoflagellates. Trophic impacts remain unknown.